Acoustic response luminescent composite nanomaterial and preparation method and application thereof

By loading the europium-doped barium titanate nanoparticles on the hollow mesoporous silica nanoparticles, the existing acoustic-responsive luminescent materials have high cost, complex preparation and poor stability, realizing sound intensity detection and temperature stability, making them suitable for industrial production.

CN119875636AActive Publication Date: 2025-04-25BIOGENOUS BIOTECH INC

Patent Information

Application Number
CN202510115548.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-25
Estimated Expiration
2045-01-24

AI Technical Summary

Technical Problem

The existing acoustic-responsive luminescent materials have problems such as high cost, complex preparation and poor stability, and it is difficult to provide a nanomaterial with low cost, simple preparation and good acoustic response sensitivity and high stability.

Method used

A composite material of hollow mesoporous silica nanoparticles and europium-doped barium titanate nanoparticles is used to generate a luminescence spectrum through laser excitation at a specific wavelength, and the sound intensity is used to change the luminescence intensity to achieve sound intensity detection.

Benefits of technology

It realizes the function of sound intensity detection, and has good temperature stability, low cost and simple preparation, which is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875636A_ABST
    Figure CN119875636A_ABST
Patent Text Reader

Abstract

The invention discloses an acoustic response light-emitting composite nanomaterial as well as a preparation method and application thereof, and belongs to the technical field of light-emitting composite nanomaterials. The acoustic response luminescent composite nano material provided by the invention comprises hollow mesoporous silica nano particles and europium-doped barium titanate nano particles loaded on the surfaces of the hollow mesoporous silica nano particles and in mesopores; the chemical formula of the europium-doped barium titanate nanoparticles is BaTiO3: Eu < 3 + >; the mass ratio of the hollow mesoporous silica nanoparticles to the europium-doped barium titanate nanoparticles is 1: (0.8-1.5). The sound response luminescent composite nano material provided by the invention can realize detection of sound intensity, and has good temperature stability, and meanwhile, the preparation method is simple and low in cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of luminescent composite nanomaterials, and in particular to an acoustically responsive luminescent composite nanomaterial and a preparation method and application thereof. Background Art

[0002] The information disclosed in the background of the invention is only intended to enhance the understanding of the overall background of the invention and should not be necessarily regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] In recent years, luminescent materials have shown great application potential in many fields, such as light-emitting devices, anti-counterfeiting, sensing, detection, disease diagnosis and other fields. As a type of luminescent material, acoustically responsive luminescent materials can have their luminescent color and intensity regulated by external acoustic stimulation. This characteristic makes this type of material have broad application prospects in sensors, bioimaging, environmental monitoring and other fields. Although acoustically responsive luminescent materials show great application potential, there is currently little research on acoustically responsive luminescent materials, and there are problems such as high cost, complex material preparation, and poor stability. Therefore, how to provide an acoustically responsive luminescent nanomaterial with low cost, simple preparation method, good acoustic response sensitivity and high stability is an urgent problem to be solved. Summary of the invention

[0004] In view of this, the present invention provides an acoustically responsive luminescent composite nanomaterial, a preparation method and an application thereof. The acoustically responsive luminescent composite nanomaterial provided by the present invention can produce a luminescent spectrum under the excitation of a laser of a specific wavelength, and the luminescent spectrum changes with the change of sound intensity, thereby being able to detect the sound intensity. At the same time, its luminescent intensity has good temperature stability.

[0005] In a first aspect, the present invention provides an acoustically responsive luminescent composite nanomaterial, comprising hollow mesoporous silica nanoparticles and europium-doped barium titanate nanoparticles loaded on the surface and in the mesopores of the hollow mesoporous silica nanoparticles; the chemical formula of the europium-doped barium titanate nanoparticles is BaTiO3:Eu 3+ ; The mass ratio of the hollow mesoporous silica nanoparticles to the europium-doped barium titanate nanoparticles is 1: (0.8~1.5).

[0006] In a second aspect, the present invention provides a method for preparing the above-mentioned acoustically responsive luminescent composite nanomaterial, comprising the following steps: Dissolving europium salt and barium salt in water to form solution 1; mixing tetrabutyl titanate, acetic acid and ethanol to form solution 2; mixing solution 1 and solution 2, and then adding hollow mesoporous silica nanoparticles, stirring at 40-60° C. for 20-60 minutes, and then heating to 100-130° C. and standing for 8-20 hours to form a precursor material; The precursor material is sintered to obtain the acoustically responsive luminescent composite nanomaterial.

[0007] In a third aspect, the present invention provides an application of the above-mentioned acoustically responsive luminescent composite nanomaterial, wherein the acoustically responsive luminescent composite nanomaterial is used to prepare an acoustic sensor.

[0008] Compared with the prior art, the present invention has achieved the following beneficial effects: (1) The luminescence intensity of the acoustically responsive luminescent composite nanomaterial provided by the present invention at an excitation wavelength of 390-400 nm increases significantly with the increase of the sound volume, and shows a good linear relationship, thereby enabling the detection of sound intensity; at the same time, the acoustically responsive luminescent composite nanomaterial of the present invention exhibits good temperature stability, and the luminescence intensity basically does not change significantly in the range of room temperature to 300°C; in addition, the acoustically responsive luminescent composite nanomaterial of the present invention has a small particle size, so that it has good application prospects in the fields of bioimaging, acoustic sensors, etc. (2) The preparation method of the acoustically responsive luminescent composite nanomaterial provided by the present invention is simple and low-cost, and is conducive to industrial large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] The drawings constituting part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute an improper limitation of the present invention. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0010] Figure 1 is a scanning electron microscope image of the hollow mesoporous silica nanoparticles prepared in Example 1 of the present invention; Figure 2 It is BaTiO3:Eu prepared in Example 2 of the present invention 3+ @Scanning electron microscope image of SiO2 nanoparticles; Figure 3 It is BaTiO3:Eu prepared in Example 2 of the present invention 3+ @Energy spectrum of SiO2 nanoparticles; Figure 4 It is BaTiO3:Eu prepared in Example 2 of the present invention 3+ @X-ray diffraction pattern of SiO2 nanoparticles; Figure 5 The BaTiO3:Eu prepared in the comparative example of the present invention 3+ SEM images of powders; Figure 6 The BaTiO3:Eu prepared in the comparative example of the present invention 3+Emission spectrum of the powder under a laser light source of 395nm and 4W power; Figure 7 It is BaTiO3:Eu prepared in Example 2 of the present invention 3+ @Emission spectrum of SiO2 nanoparticles under a laser light source of 395nm and 4W power; Figure 8 The BaTiO3:Eu prepared in the comparative example of the present invention 3+ Powder and BaTiO3:Eu of Example 2 3+ @Fourier infrared absorption spectrum of SiO2 nanoparticles; Fig. 9 It is BaTiO3:Eu of Example 2 of the present invention 3+ @Emission spectra of SiO2 nanoparticles at different sound intensities; Fig.10 It is BaTiO3:Eu of Example 2 of the present invention 3+ @The luminescence intensity of SiO2 nanoparticles at 592.8nm changes with sound intensity; Fig.11 It is BaTiO3:Eu of Example 2 of the present invention 3+ @The luminescence intensity of SiO2 nanoparticles at 616.2nm changes with sound intensity; Fig.12 It is BaTiO3:Eu of Example 2 of the present invention 3+ @The fluorescence intensity of SiO2 nanoparticles at 616.2nm changes with temperature; Fig.13 It is BaTiO3:Eu of Example 2 of the present invention 3+ @ Fluorescence imaging of SiO2 nanoparticles in Hela cells, where (a) is a bright field image of Hela cells and (b) is a bright field image of BaTiO3:Eu 3+ @SiO2 nanoparticle fluorescence imaging, (c) Hela cell bright field image and BaTiO3:Eu 3+ @Overlay of fluorescence imaging of SiO2 nanoparticles. DETAILED DESCRIPTION

[0011] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0012] The present invention provides an acoustically responsive luminescent composite nanomaterial, comprising hollow mesoporous silica nanoparticles and europium-doped barium titanate nanoparticles loaded on the surface and in the mesopores of the hollow mesoporous silica nanoparticles; the chemical formula of the europium-doped barium titanate nanoparticles is BaTiO3:Eu 3+ ; The mass ratio of the hollow mesoporous silica nanoparticles to the europium-doped barium titanate nanoparticles is 1: (0.8~1.5).

[0013] In the acoustically responsive luminescent composite nanomaterial provided by the present invention, europium-doped barium titanate nanoparticles, as a piezoelectric material, generate electric charges when subjected to acoustic wave pressure, and this piezoelectric effect converts the acoustic wave signal into an electrical signal; when sound excites the barium titanate nanoparticles, it can produce a nonlinear optical effect under the acoustic wave, resulting in luminescence. The energy of the acoustic wave promotes electron transitions and generates photons, so the sound intensity can be detected by measuring the fluorescence intensity of the luminescence spectrum. The present invention loads it on the surface and in the mesopores of hollow mesoporous silica nanoparticles, which can not only obtain nanoparticles with a smaller particle size, expand its application in the fields of biological imaging, but also improve its stability. Moreover, europium-doped barium titanate nanoparticles only need to be added in a small amount to exert a higher sensitivity for sound intensity detection, with low cost and good application prospects.

[0014] In the present invention, the average particle size of the acoustic response luminescent composite nanomaterial is 60-150 nm. The smaller particle size enables the nanoparticles to have a higher specific surface area, thereby enhancing the acoustic wave interaction effect and the piezoelectric effect, and being able to better reflect the acoustic response characteristics.

[0015] In the present invention, the europium-doped barium titanate nanoparticles have Ti 4+ With Eu 3+ The molar ratio of Eu to Ti is (80-92):(8-20). Eu is used as a doping element to replace part of the Ti element, so the total molar amount of the Ti element and the Eu element is the same as the molar amount of the Ba element.

[0016] The present invention also provides a method for preparing the above-mentioned acoustically responsive luminescent composite nanomaterial, comprising the following steps: Dissolving europium salt and barium salt in water to form solution 1; mixing tetrabutyl titanate, acetic acid and ethanol to form solution 2; mixing solution 1 and solution 2, and then adding hollow mesoporous silica nanoparticles, heating to 40-60° C. and stirring for 20-60 minutes, and then heating to 100-130° C. and standing for 8-20 hours to form a precursor material; The precursor material is sintered to obtain the acoustically responsive luminescent composite nanomaterial.

[0017] In the present invention, since the hollow mesoporous silica nanoparticles contain a mesoporous structure, when they are added to a mixed solution containing solution one and solution two, europium salts, barium salts and tetrabutyl titanate will enter the pores of the hollow mesoporous silica nanoparticles, and in situ grow europium-doped barium titanate nanoparticles during the subsequent reaction and sintering process; in the absence of hollow mesoporous silica nanoparticles, the above preparation method will obtain micron-sized europium-doped barium titanate particles.

[0018] In the present invention, the europium salt is selected from europium chloride, europium nitrate or europium acetate, and the barium source is selected from barium acetate, barium chloride or barium nitrate.

[0019] In the present invention, after the step of adding the hollow mesoporous silica nanoparticles, ultrasonic treatment is first performed, and then vacuuming is performed; wherein the ultrasonic power is 80-200W, the ultrasonic time is 5-20 minutes, and the vacuuming time is 10-20 minutes, and the vacuuming is performed until no bubbles are generated. Ultrasonic treatment and vacuuming can promote more solutes to penetrate into the pores of the hollow mesoporous silica nanoparticles.

[0020] In the solution 1 of the present invention, the concentration of europium salt is 0.8-1.5 mol / L; the dosage ratio of tetrabutyl titanate, acetic acid and ethanol is 10 mmol: (4-6) mL: (2-4) mL. The addition amount of europium salt, barium salt, tetrabutyl titanate and hollow mesoporous silica nanoparticles is determined according to the molar ratio and mass ratio of the acoustically responsive luminescent composite nanomaterial.

[0021] The present invention does not impose any special limitation on the source of the hollow mesoporous silica nanoparticles, which can be purchased or homemade. The present invention does not impose any special limitation on the preparation method thereof, which can be prepared by the preparation method of hollow mesoporous silica nanoparticles commonly used by technicians in the field. The present invention preferably adopts the sol-gel method for preparation.

[0022] In the present invention, the sintering includes pre-sintering and formal sintering. The temperature of the pre-sintering is 400~600℃. The pre-sintering is to improve the composition and structure of the material and ensure its volume stability; the temperature of the formal sintering is 1100~1300℃. The formal sintering further improves the stability of the material and makes it a tetragonal phase. Furthermore, the time of the pre-sintering is 1~3h, and the time of the formal sintering is 1~3h. After the pre-sintering is completed, the temperature is lowered to room temperature, the pre-sintered product is taken out for grinding, and then formal sintering is performed; the grinding time is 3~10min. The present invention does not impose any special restrictions on the heating rate of heating to the pre-sintering temperature, and the present invention is preferably 2~30℃ / min; the present invention does not impose any special restrictions on the heating rate of heating to the formal sintering temperature, and the present invention is preferably 3~10℃ / min.

[0023] In the present invention, after the formal sintering step, the sintered product is further washed, dried and ground, and the acoustically responsive luminescent composite nanomaterial is obtained after grinding. The washing process is centrifugal washing with water to remove unreacted raw materials, and the washing is performed 1 to 3 times. The present invention does not impose any special restrictions on the drying process, and a drying method commonly used in the art can be used. The present invention also does not impose any special restrictions on the grinding process, and the grinding time is preferably 40 to 90 minutes.

[0024] The present invention provides an application of the acoustically responsive luminescent composite nanomaterial, wherein the acoustically responsive luminescent composite nanomaterial is used to prepare an acoustic sensor.

[0025] The technical solution of the present invention is further described below in conjunction with specific examples. The present invention has no special restrictions on the sources of the reagents used in the following examples, and commercial products known to those skilled in the art can be used. The room temperature in the following examples refers to 25±3°C.

[0026] Example 1 This embodiment provides a method for preparing mesoporous silica (SiO2).

[0027] (1) Preparation of solid silica spheres (sSiO2): Add 10mL of water, 69.4mL of ethanol, and 2.2mL of ammonia water (25wt%) to beaker A and stir for 10 minutes. Then take 2mL of tetraethyl orthosilicate (TEOS) and 2mL of ethanol, ultrasonically homogenize, add them to beaker A at a flow rate of 1mL / min using a peristaltic pump, and stir for 1h. After centrifugation, wash once with water and once with ethanol. Dissolve in 21mL of water, ultrasonically disperse evenly, and obtain sSiO2 aqueous dispersion.

[0028] (2) Preparation of hollow mesoporous silica nanoparticles (HMSNs): Add 60 mg triethylamine (TEA), 6 g hexadecyltrimethylammonium chloride (CTAC) and 60 mL water to round-bottom flask A and stir for 1 h. Add the sSiO2 aqueous dispersion of step (1) to round-bottom flask A and stir at room temperature for 1 h. Use a peristaltic pump to add 0.45 mL TEOS, stir at 80 ° C for 1 h, and cool to 50 ° C. Add 5.8362 g CTAC and 1.8550 g Na2CO3 to round-bottom flask A and stir at 50 ° C for 0.5 h. Centrifuge at high speed, wash twice with water, and wash twice with ethanol. Then reflux the product at 80 ° C for 8 h in an alcohol acid solution (0.8 mL of 12 mol / L concentrated hydrochloric acid dissolved in 100 mL ethanol) and cool to room temperature. Centrifuge at 9000 r / min*10 min, wash once with ethanol, wash once with water, and dry to obtain hollow mesoporous silica nanoparticles (HMSNs).

[0029] Figure 1This is a scanning electron microscope image of the hollow mesoporous silica nanoparticles prepared in this example. It can be seen from the image that the hollow mesoporous silica nanoparticles (HMSNs) are spherical and have a particle size of 80-150 nm.

[0030] Example 2 This embodiment provides an acoustically responsive luminescent composite nanomaterial BaTiO3:Eu 3+ @Preparation method of SiO2.

[0031] (1) Weigh 2.1711 g of barium acetate Ba(AC)2 (8.5 mmol) and add it to beaker A. Use a pipette to add 1500 µL of europium chloride (1 mol / L) to beaker A. Then add 7.2 mL of deionized water and stir vigorously until the solution becomes clear.

[0032] (2) Mix 10 mmol of tetrabutyl titanate, 5.1 mL of acetic acid, and 3.3 mL of ethanol in beaker B and stir vigorously until the solution becomes clear; then drop the solution in beaker A into beaker B and stir to obtain a mixed solution.

[0033] (3) Take one twentieth of the mixed solution (1 mL), add 100 mg of hollow mesoporous silica, and ultrasonically treat for 10 min at an ultrasonic power of 100 W; then vacuumize for about 15 minutes; then transfer to an evaporating dish, heat to 50 ° C, stir for 40 min, and stand at 120 ° C for 12 h to obtain the precursor material.

[0034] (4) The precursor material was heated to 500°C at a heating rate of 5°C / min and pre-calcined for 2h. After cooling to room temperature, it was taken out and ground for 5min, and then heated to 1200°C at a heating rate of 8°C / min and calcined for 2h. After the material cooled to room temperature, it was centrifuged at 12000r / min for 10min, washed once with water, dried, and then ground in an agate mortar for 1h to obtain the purified BaTiO3:Eu 3+ @SiO2 powder.

[0035] Figure 2 The BaTiO3:Eu prepared in this embodiment is provided. 3+ @Scanning electron microscope image of SiO2 nanoparticles shows that the nanoparticles are spherical and have a particle size between 100 and 150 nm.

[0036] Figure 3 The BaTiO3:Eu prepared in this embodiment is provided. 3+ @The energy spectrum of SiO2 nanoparticles shows that the nanoparticles contain four elements: Ba, Ti, O, and Eu, indicating that BaTiO3:Eu 3+ Nanoparticles are loaded on the surface of SiO2.

[0037] Figure 4 The BaTiO3:Eu prepared in this embodiment is provided. 3+ @X-ray diffraction pattern of SiO2 nanoparticles, BaTiO3:Eu 3 + The XRD pattern of @SiO2 nanoparticles is completely consistent with the standard card (PDF#75-1606), indicating that the prepared BaTiO3:Eu 3+ @SiO2 nanoparticles are pure phase and do not have any impurities.

[0038] Comparative Example This comparative example provides BaTiO3:Eu 3+ Preparation of powder (without SiO2).

[0039] (1) Weigh 2.1711 g of barium acetate Ba(AC)2 (8.5 mmol) and add it to beaker A. Use a pipette to add 1500 µL of europium chloride (1 mol / L) to beaker A. Then add 7.2 mL of deionized water and stir vigorously until the solution becomes clear.

[0040] (2) Mix 10 mmol of tetrabutyl titanate, 5.1 mL of acetic acid, and 3.3 mL of ethanol in beaker B and stir vigorously until the solution becomes clear.

[0041] (3) The solution in beaker A was dripped into beaker B, and then transferred to an evaporating dish. The mixture was stirred at 50°C for 40 min, and then allowed to stand at 120°C for 12 h to obtain a precursor material.

[0042] (4) The precursor material was heated to 500°C at a heating rate of 5°C / min and pre-calcined for 2h. After cooling to room temperature, it was taken out and ground for 5min, and then heated to 1200°C at a heating rate of 8°C / min and calcined for 2h. After the material cooled to room temperature, it was centrifuged at 12000r / min for 10min, washed once with water, dried, and then ground in an agate mortar for 1h to obtain the purified BaTiO3:Eu 3+ powder.

[0043] Figure 5 BaTiO3:Eu prepared in this comparative example 3+ The scanning electron microscope image of the powder shows that BaTiO3:Eu 3+ It is cubic in shape, with an edge length of about 1 μm.

[0044] Figure 6 and Figure 7 The BaTiO3:Eu prepared in this comparative example are 3+ Powder and BaTiO3:Eu prepared in Example 2 3+@SiO2 nanoparticles emission spectrum under 395nm, 4W laser light source, it can be seen that the emission peak positions of the two are slightly different, with orange light emission peaks appearing around 593nm and red light emission peaks appearing around 616nm. 3+ @The red light emission intensity of SiO2 nanoparticles is enhanced, indicating that SiO2 has a certain influence on its luminescence performance, which is beneficial to improving the luminescence efficiency.

[0045] Figure 8 The BaTiO3:Eu prepared in this comparative example is provided. 3+ Powder and BaTiO3:Eu of Example 2 3+ @SiO2 nanoparticles Fourier transform infrared absorption spectrum (FTIR) diagram, from which we can see that BaTiO3:Eu 3+ The surface absorption peak is 1441.93 cm -1 , BaTiO3:Eu 3+ The absorption peaks of @SiO2 surface are 1436.97 cm -1 、1087.46 cm -1 , 1436.97 cm -1 The absorption peak at corresponds to TiO3 2- Stretching vibration of Ti-O bond in , 1087.46 cm -1 The absorption peak at is related to the stretching vibration of Si-O bond. The existence of Si-O bond indicates that BaTiO3:Eu 3+ Combined with SiO2 through chemical reaction.

[0046] Test example 1. BaTiO3:Eu in Example 2 3+ @SiO2 nanoparticles are used for acoustic response, the specific steps are as follows: The BaTiO3:Eu in Example 2 3+ @SiO2 nanoparticles were placed in a fluorescence / phosphorescence / luminescence spectrophotometer (F-7000) and their emission spectra were measured without external sound interference. By adjusting the volume of the mobile phone, the emission spectra at 30-100dB were measured (the excitation light source was 395nm and the power was 4W), and the results were Fig. 9 The emission spectra for different sound intensities are shown in Figure 1. Fig.10 BaTiO3:Eu 3+ @The luminescence intensity of SiO2 nanoparticles at 592.8nm changes with sound intensity. Fig.11 BaTiO3:Eu 3+ @SiO2 nanoparticles luminescence intensity at 616.2nm changes with sound intensity. It can be seen that as the sound intensity increases, BaTiO3:Eu3+ @SiO2 nanoparticles have a higher luminescence intensity and show a better linear relationship, so they can be used to prepare acoustic sensors to detect sound intensity.

[0047] 2. Temperature stability test: Take the BaTiO3:Eu of Example 2 3+ @SiO2 nanoparticles are placed in a temperature-variable device, the position of the temperature-variable device is fixed, and then the temperature-variable device is heated (30~300℃). Under laser irradiation with an excitation power of 4W and an excitation wavelength of 395nm, the fluorescence emission spectrum of the luminescent composite nanomaterial is tested using a steady-state-transient fluorescence spectrometer to obtain a curve of the fluorescence intensity of the nanoparticles at 616.2nm changing with temperature, as shown in Fig.12 As shown, it can be seen that the fluorescence intensity fluctuates very little with the increase of temperature and remains basically stable, indicating that the prepared luminescent composite nanomaterial has good temperature stability.

[0048] 3. Fluorescence imaging experiment: The materials in Example 2 were used in a fluorescence imaging experiment, and the specific steps were as follows: (1) Using UV light to prepare BaTiO3:Eu 3+ @SiO2 nanoparticles (300 mg) were sterilized and dispersed in 15 mL of Hela cell (human cervical cancer cell) DMEM culture medium.

[0049] (2) Hela cells were cultured at 5×10 3 The cells were inoculated into 96-well plates at a density of 100 cells / well and incubated overnight in a 5% CO2, 37°C environment to ensure cell adhesion. 3 mg of BaTiO3:Eu was added to each well. 3+ @SiO2 nanoparticles in DMEM medium and incubate for 2h.

[0050] (3) The cells were fixed with 4 wt% paraformaldehyde and the BaTiO3:Eu was observed using an inverted fluorescence microscope. 3+ @Fluorescence imaging of SiO2 nanoparticles in cells.

[0051] Take cell bright field and material fluorescence images separately, and finally combine the two to get a superimposed image, such as Fig.13 As shown, Fig.13 BaTiO3:Eu prepared in Example 2 3+ @SiO2 fluorescence imaging in Hela cells shows that BaTiO3:Eu 3+ @Fluorescence properties of SiO2 composite nanomaterials in cell imaging.

[0052] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An acoustically responsive luminescent composite nanomaterial, characterized in that: The invention comprises hollow mesoporous silica nanoparticles and europium-doped barium titanate nanoparticles loaded on the surface and in the mesopores of the hollow mesoporous silica nanoparticles; the chemical formula of the europium-doped barium titanate nanoparticles is BaTiO3:Eu 3+ ; The mass ratio of the hollow mesoporous silica nanoparticles to the europium-doped barium titanate nanoparticles is 1: (0.8~1.5).

2. The acoustically responsive luminescent composite nanomaterial according to claim 1, characterized in that: The average particle size of the acoustic response luminescent composite nanomaterial is 60-150 nm.

3. The acoustically responsive luminescent composite nanomaterial according to claim 1, characterized in that: In the europium-doped barium titanate nanoparticles, Ti 4+ With Eu 3+ The molar ratio is (80~92):(8~20).

4. The method for preparing the acoustically responsive luminescent composite nanomaterial according to any one of claims 1 to 3, characterized in that: The steps include: Dissolving europium salt and barium salt in water to form solution 1; mixing tetrabutyl titanate, acetic acid and ethanol to form solution 2; mixing solution 1 and solution 2, and then adding hollow mesoporous silica nanoparticles, heating to 40-60° C. and stirring for 20-60 minutes, and then heating to 100-130° C. and standing for 8-20 hours to form a precursor material; The precursor material is sintered to obtain the acoustically responsive luminescent composite nanomaterial.

5. The preparation method according to claim 4, characterized in that: The europium salt is selected from europium chloride, europium nitrate or europium acetate, and the barium source is selected from barium acetate, barium chloride or barium nitrate.

6. The preparation method according to claim 4, characterized in that: In the solution 1, the concentration of europium salt is 0.8-1.5 mol / L; the dosage ratio of tetrabutyl titanate, acetic acid and ethanol is 10 mmol: (4-6) mL: (2-4) mL.

7. The preparation method according to claim 4, characterized in that: After the step of adding the hollow mesoporous silica nanoparticles, ultrasonic treatment is first performed and then vacuuming is performed; wherein the ultrasonic power is 80-200W, the ultrasonic time is 5-20min, and the vacuuming time is 10-20min.

8. The preparation method according to claim 4, characterized in that: The sintering includes pre-sintering and formal sintering. The pre-sintering temperature is 400-600° C., and the pre-sintering time is 1-3 hours. The formal sintering temperature is 1100-1300° C., and the formal sintering time is 1-3 hours.

9. The preparation method according to claim 8, characterized in that: After the formal sintering step, the method further includes the steps of washing, drying and grinding the sintered product, and the acoustically responsive luminescent composite nanomaterial is obtained after grinding.

10. Use of the acoustically responsive luminescent composite nanomaterial according to any one of claims 1 to 3 or the acoustically responsive luminescent composite nanomaterial prepared by the preparation method according to any one of claims 4 to 9, characterized in that: The acoustic response luminescent composite nanomaterial is used to prepare an acoustic sensor.

Citation Information

Patent Citations

  • Preparation method and application of curcumin-loaded glucan-modified gadolinium-doped hollow mesoporous silica nano-material

    CN109010850A

  • Manganese-doped hollow mesoporous silica nano material as well as preparation method and application thereof

    CN114394602A

  • Mesoporous barium titanate nano material and preparation method and application thereof

    CN117602667A

Cited By

  • Piezoelectric fluorescent composite material and preparation method and application thereof

    CN121652802A

  • Piezoelectric fluorescent composite material, preparation method and application thereof

    CN121652802B